Perkembangan Psikomotorik Pada Anak Autis Di SLB Muatiara Bunda Kota Bengkulu - Uliza, Eli Fitri; Noptami, Hanifa Sholeha; Anjani, Ola; Ulandari, Rahma; Mardiani, Yena; Zubaidah, Zubaidah (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2024)
Psychomotor development is a development that focuses on controlling human body movements through the coordinated activity of the central nervous system, peripheral nerves and muscles. Children with special needs are children who require special learning methods and services that are different from other children. Meanwhile, autists are sufferers of Autism which is defined as a childhood disorder characterized by delays in cognition, communication, behavior and social interaction. Our focus in this research is 1). How is the psychomotor development of autistic children at SLB Mutiara Bunda, Bengkulu City? 2). How do teachers improve psychomotor development in autistic children at SLB Mutiara Bunda, Bengkulu City? The objectives of this research are, 1). To find out how psychomotor development occurs in autistic children at SLB Mutiara Bunda, Bengkulu city. 2). To find out how teachers can improve psychomotor development in autistic children at SLB Mutiara Bunda, Bengkulu city. This type of research uses a qualitative approach using data source techniques originating from three types of sources: data collection techniques in the form of observation, interviews, and documentation.